2003
DOI: 10.1002/anie.200352565
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Switching between Superhydrophilicity and Superhydrophobicity

Abstract: From soaking wet to bone dry: The concept of reversible switching between superhydrophilicity and superhydrophobicity of a surface (see picture) exploits the thermally responsive wettability of poly(N‐isopropylacrylamide), and this property is enhanced by surface roughness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
870
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,077 publications
(895 citation statements)
references
References 38 publications
23
870
1
1
Order By: Relevance
“…Poly(N-substituted acrylamide) (PNIPAAm) is the most popular temperature-responsive polymer because of its sharp phase transition in water at around 32 8C. [109] The NIPAAm segment can been designed to control the lower critical solution temperature (LCST) as well as the response kinetics at the molecular level. Thus, NIPAAm is a suitable target molecule for responsive films.…”
Section: Single-responsive Interfacesmentioning
confidence: 99%
“…Poly(N-substituted acrylamide) (PNIPAAm) is the most popular temperature-responsive polymer because of its sharp phase transition in water at around 32 8C. [109] The NIPAAm segment can been designed to control the lower critical solution temperature (LCST) as well as the response kinetics at the molecular level. Thus, NIPAAm is a suitable target molecule for responsive films.…”
Section: Single-responsive Interfacesmentioning
confidence: 99%
“…[66] Besides, because the liquid-transport ability can be controlled by manipulating the surface wettability, smart peristome-inspired surfaces can be prepared by constructing stimulus-responsive materials on the surfaces. [60,67,68] This will result in a controllable liquid flow on the surface, showing wide applications in mechanical engineering, including in controllable self-lubrication (Figure 4c), and heat or mass transfer. [69] In addition, one of the important applications of peristome-mimetic structures could be in microfluidics, [70] and the unidirectional liquid transport on the biomimetic structure in channels could be used for smart and controllable microfluidic devices (Figure 4d), for example, the lab-on-a-chip.…”
Section: Applications Of Peristome-inspired Surfacesmentioning
confidence: 99%
“…Electrochemical switching in polymers is expected to affect the strength and the density of dipoles and the binding characteristics of doping ions. Thus, by modifying the electrochemical switch, it is possible to achieve electronic control over the surface tension (Isaksson et al 2004;Sun et al 2004;Causley et al 2005;Robinson et al 2006). It has also been reported that the wetting and adhesive properties of an electroactive polymer can be varied by changing its oxidation state.…”
Section: Physical -Chemical Modificationsmentioning
confidence: 99%